Experimenter Effects on Pain Reporting in Women Vary across the Menstrual Cycle - Jacob M. Vigil; Jared DiDomenico; Chance Strenth; Patrick Coulombe; Eric Kruger; Andrea A. Mueller; Diego Guevara Beltran; Ian Adams (International Journal of Endocrinology)
Background. Separate lines of research have shown that menstrual cycling and contextual factors such as the gender of research personnel influence experimental pain reporting. Objectives. This study examines how brief, procedural interactions with female and male experimenters can affect experimentally reported pain (cold pressor task, CPT) across the menstrual cycle. Methods. Based on the menstrual calendars 94 naturally cycling women and 38 women using hormonal contraceptives (Mage=19.83,  SD=3.09) were assigned to low and high fertility groups. This assignment was based on estimates of their probability of conception given their current cycle day. Experimenters (12 males, 7 females) engaged in minimal procedural interactions with participants before the CPT was performed in solitude. Results. Naturally cycling women in the high fertility group showed significantly higher pain tolerance (81 sec, d=.79) following interactions with a male but not a female experimenter. Differences were not found for women in the low fertility or contraceptive groups. Discussion. The findings illustrate that menstrual functioning moderates the effect that experimenter gender has on pain reporting in women. Conclusion. These findings have implications for standardizing pain measurement protocols and understanding how basic biopsychosocial mechanisms (e.g., person-perception systems) can modulate pain experiences.